2009
DOI: 10.1089/dia.2009.0058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insulin Catheter Wear-Time on Subcutaneous Adipose Tissue Blood Flow and Insulin Absorption in Humans

Abstract: Insertion of a Teflon insulin catheter into the SAT results in increased ATBF and faster absorption of insulin aspart in a period of 4 days without any change in the total amount of insulin aspart absorbed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 33 publications
4
41
1
Order By: Relevance
“…These results were generally consistent with the finding that local blood flow at an infusion site increases in the first 3 days (leading to accelerated insulin pharmacokinetics), but decreases after that. 16 Our results agree with the past literature that on average, day 3 is an appropriate recommendation for changing infusion sets, [16][17][18][19][20] although individual variations exist.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results were generally consistent with the finding that local blood flow at an infusion site increases in the first 3 days (leading to accelerated insulin pharmacokinetics), but decreases after that. 16 Our results agree with the past literature that on average, day 3 is an appropriate recommendation for changing infusion sets, [16][17][18][19][20] although individual variations exist.…”
Section: Discussionsupporting
confidence: 92%
“…17 Additionally, mean daily blood glucose has been documented to increase with the number of days of infusion set use. [16][17][18][19][20] We have found that there is considerable variability in the duration of set survival for individual subjects in this study (Fig. 1B).…”
Section: Discussionmentioning
confidence: 96%
“…There was no single specific event related to an extended catheter use but events of all kinds and nature occurred after day 3, including but not limited to pulling out, kinking, adhesive getting loose, leakage of insulin from the infusion set or the infusion site, and signals of skin irritation, such as bruising, redness, or swelling. Even when the patients locally tolerated a longer use of the infusion sets at the infusion site for up to 7 days, there appeared to be changes in the insulin absorption leading to a slow but steady loss in glycemic control with increased duration of use, as indicated by a steady increase in mean daily blood glucose concentrations, which is in line with a most recent observational study by Perrin et al 11,12 In general, potential problems that may occur in adult and adolescent patients when using the infusion sets longer than the recommended 48-72 hours may be technical problems, such as catheter occlusions or kinking, 13,14 bacterial contaminations leading to skin inflammation, [15][16][17] potential changes in physicochemical delivery characteristics, 18,19 and local skin reactions to the adhesive, resulting in redness, itching, and other symptoms of skin irritation. 12 The purpose of this study was to evaluate the safety and efficacy of using infusion sets for 2 days versus 4 days during a period of 3 months each in a prospective and randomized crossover protocol in patients with type 1 diabetes.…”
supporting
confidence: 72%
“…9,10 While the cause for this effect was not determined, we speculated that increased blood flow and/or foreign body reaction might be playing a role. More recently, Clausen and colleagues 11 demonstrated such an increase in blood flow around the insulin infusion site from day 1 until day 4 in healthy adults. Techniques mimicking the changes in the aged infusion site to increase insulin absorption and action without adverse effects will be ideal options to generate a UFI profile.…”
Section: Advances In Insulin Therapy: Introduction Of Rapid-acting Inmentioning
confidence: 94%